Lattice structure of torsion classes for path algebras. (8th October 2015) - Iyama, Osamu; Reiten, Idun; Thomas, Hugh; Todorov, Gordana
Abstract : We consider module categories of path algebras of connected acyclic quivers. It is shown in this paper that the set of functorially finite torsion classes form a lattice if and only if the quiver is either Dynkin quiver of type A, D, E, or the quiver has exactly two vertices.